2018
DOI: 10.1128/aac.01852-17
|View full text |Cite
|
Sign up to set email alerts
|

Mutations at the Ribosomal S10 Gene in Clinical Strains of Staphylococcus aureus with Reduced Susceptibility to Tigecycline

Abstract: Mutations on the tip of the extended loop of the ribosomal S10 protein have been associated to tigecycline (TGC) resistance in passaged mutants of different bacteria species. This study described the first two clinical TGC-resistant isolates with these mutations. One strain (TGC MIC = 2 mg/liter) had a 12-nucleotide deletion affecting residues 56 to 59 (HKYK) of the S10 protein. The second strain (TGC MIC = 1 mg/liter) had amino acid substitutions (K57M and Y58F) previously described in passaged mutants.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 9 publications
0
14
0
Order By: Relevance
“…A K57M amino acid substitution in the ribosomal S10 gene was detected in CP3_late genome. Remarkably, two clinical S. aureus isolates with mutation in this same region of the S10 protein (a deletion of residues 56 to 59; and double mutant K57M, Y58F) have been recently shown to confer resistance to tigecyclin [46].…”
Section: Resultsmentioning
confidence: 99%
“…A K57M amino acid substitution in the ribosomal S10 gene was detected in CP3_late genome. Remarkably, two clinical S. aureus isolates with mutation in this same region of the S10 protein (a deletion of residues 56 to 59; and double mutant K57M, Y58F) have been recently shown to confer resistance to tigecyclin [46].…”
Section: Resultsmentioning
confidence: 99%
“…Recent crystallographic analysis studies have revealed the same mechanism of the new-generation tetracycline class antibiotics, including Tige, Omada and Erava, to inhibit bacterial protein synthesis by binding to the 30S ribosomal subunits, including 16SrRNA and 30S ribosome protein S10 [8,18]. Previous researches indicated that genetic mutations affecting the 30S ribosome subunits (i.e., 16SrRNA and ribosome proteins S10) have been shown to confer resistance to Tige and Omada in S. aureus [9][10][11][12][13][14][15][16][17]18]. However, the characteristics of genetic mutation of the 30S ribosome subunits and cross resistance in Erava resistant S. aureus remains unknown.…”
Section: Discussionmentioning
confidence: 99%
“…Meanwhile, our study revealed high frequency of genetic mutations in 30S ribosome protein S10 in Erava-derived resistant isolates, indicating this protein might be an important factor in Erava resistance evolution. Previous multiple reports have shown that the mutation in 30S ribosome protein S10 of S. aureus can result in the MIC elevation of tetracycline, Omada and Tige, indicating its important role in the resistance evolution of tetracycline class drugs [6,9,12,13,15,17]. Therefore, the cross resistance under Erava pressure with Omada and Tige might be mainly explained by the genetic mutation of 30S ribosome subunits The frequent occurrence of antibiotics heteroresistance can result in the treatment failure.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Tigecycline is the first semi-synthetic antibiotic under the minocycline antibiotic class. Studies have reported MRSA to have overexpression of efflux pump through the mutations of both mep R and mep A genes resulting in overexpression of mep A and derepression of mep R. Furthermore, studies have shown the mutation of the ribosomal protein at S10 (Argudín et al, 2018 ). Study by Dabul et al ( 2018 ) found out that mutation in rpsJ was not observed in their MRSA strain studied, but only the efflux mechanism was determined (Dabul et al, 2018 ).…”
Section: The Mechanisms Of Antibiotic Resistance In Mrsamentioning
confidence: 99%